Antioxidant potential of coffee husks in fresh pork sausage - Araya Morice, Adriana (2023)
Coffee husks, a by-product of dry coffee processing, present a disposal problem in coffee-producing countries. Valorization of this residue is necessary to reduce its environmental impact and improve benefits to the producer. This study evaluated the antioxidant effect of coffee husks on physicochemical properties and sensory liking of fresh sausages packaged in aerobic (AEP) or modified atmosphere packaging (MAP) (20% CO2 + 80%N2). Fresh sausages were prepared with different antioxidants: no addition (control C), sodium nitrite (T2), sodium nitrite + sodium erythorbate + BHA/BHT blend (T3), sodium nitrite + coffee husk 1% (T4), sodium nitrite + coffee husk 2% (T5). Physicochemical properties (TBARs, carbonyl content, pH and instrumental color) were analyzed to evaluate the effect of added synthetic and natural antioxidants on fresh sausages. A sensory test (n = 100) was conducted to assess consumer liking of fresh sausages stored in AEP and MAP. The addition of coffee husks reduced lipid oxidation in fresh sausages, especially under MAP packaging, but did not affect carbonyl content. Consumers reported lower liking scores for products packed in MAP. The addition of coffee husks did not affect the degree of liking. Valorization of coffee husks as an antioxidant in fresh meat products is a viable natural option for the meat industry.